2014
DOI: 10.1016/j.juro.2014.02.2569
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Invasion of Testicular Nonseminomatous Germ Cell Tumors: Implications of Separate Evaluation of Lymphatic and Blood Vessels

Abstract: Lymphovascular invasion in LYVE-1 stained sections was the most important predictive parameter for metastasis at diagnosis, suggesting greater relevance of the lymphatic system in metastatic dissemination of testicular nonseminomatous germ cell tumors. Vascular endothelial cell specific markers provide higher diagnostic accuracy for microvascular invasion. Our results may impact the current concept of microvascular invasion used for risk stratification of clinical stage 1 testicular nonseminomatous germ cell t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…The only factor that correlates with lower T cells counts was microvascular invasion (MVI). This situation has been attempted to relate to the possible haematogenous spread of tumor cells, and as an independent risk factor for poor prognosis in many solid tumors [33][34][35][36][37][38]. We showed a relationship between γδ T cell subsets in peripheral blood and MVI in https://doi.org/10.1371/journal.pone.0243545.g008…”
Section: Discussionmentioning
confidence: 82%
“…The only factor that correlates with lower T cells counts was microvascular invasion (MVI). This situation has been attempted to relate to the possible haematogenous spread of tumor cells, and as an independent risk factor for poor prognosis in many solid tumors [33][34][35][36][37][38]. We showed a relationship between γδ T cell subsets in peripheral blood and MVI in https://doi.org/10.1371/journal.pone.0243545.g008…”
Section: Discussionmentioning
confidence: 82%
“…There is, at the moment, no formal recommendation for performing immunohistochemistry studies for aiding in vascular invasion determination nor for the need to discriminate lymph vessel from blood vessel invasion. 24 Few studies have assessed the latter, and it remains inconclusive whether discriminating among these might have additional value; one study has shown that only lymph vessel invasion associated with prognosis (metastases at diagnosis), 48 while another paper reported the opposite scenario. 49 Furthermore, a small pilot study on 24 testicular germ cell tumors showed that ERG immunohistochemistry could be of value in confirming vascular invasion, despite showing limited clinical impact in that small and heterogenous cohort of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the previous studies on LVI appear not to have used immunochemistry routinely in its diagnosis. Although one recent article suggested that the routine use of immunochemistry to identify LVI may be helpful, further studies are needed, and at present we recommend that diagnosis should be made on haematoxylin and eosin stained slides backed up by immunochemistry for lymphovascular vessels in challenging cases …”
Section: Methodsmentioning
confidence: 99%
“…Although one recent article suggested that the routine use of immunochemistry to identify LVI may be helpful, further studies are needed, and at present we recommend that diagnosis should be made on haematoxylin and eosin stained slides backed up by immunochemistry for lymphovascular vessels in challenging cases. 44 We recommend that vascular invasion be called either present or 'not identified', as equivocation in the report is unhelpful to the clinician. We advise restricting the definition of vascular invasion so that those cases that are equivocal are assigned as 'not identified'.…”
Section: Y M P H O V a S C U L A R I N V A S I O N ( R E Q U I R E D )mentioning
confidence: 99%